ANALISIS KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR SEBELUM DAN SESUDAH PERUSAHAAN MELAKUKAN IPO (INITIAL PUBLIC OFFERING) PADA TAHUN 2015 DI BURSA EFEK INDONESIA (BEI) - Danna Solihin, 3, Muchammad Faik Chumaidi ,. Eddy Soegiarto (EKONOMIA, 2020)
Analysis Financial Performance of Manufacturing Companies Before and After the Company Conducted an Initial Public Offering (IPO) in 2015 on the Indonesia Stock Exchange (IDX). An Initial Public Offering or IPO is a stock offering for the first time to the public. Go public is a company policy that has decided to sell its shares to the public and is ready to be publicly assessed. IPO is one of the methods used by companies to obtain additional capital that is useful for the development of the company. The advantage of IPO is that companies will get additional capital that is relatively easier and automatically the company will be better known to the public. The disadvantage of IPO is that companies are required to publish company financial reports regularly to the public.This research was conducted to analyze the differences that occurred in the company's financial performance between 2 years before the IPO (2013-2014) with 2 years after the IPO (2016-2017) in manufacturing companies listed on the Indonesia Stock Exchange in 2015. Financial ratios used as variables in this study are current ratio (CR), quick ratio (QR), debt to equity ratio (DER), debt to assets ratio (DAR), return on assets (ROA), return on equity (ROE), net profit margin (NPM), total assets turnover (TAT), and working capital turnover (WCT). Analysis of the data used in this study is to compare the company's financial performance whether there is an increase or decrease after conducting an IPO using a comparison analysis table as a descriptive analysis and Paired Sample T-Test as a comparative analysis.The results of this study using a comparison analysis table and Paired Sample T-Test indicate that the current ratio (CR), return on assets (ROA), net profit margin (NPM) and working capital turnover (WCT) increase in value but not significant after the IPO and only in the quick ratio (QR) there was a significant increase after the IPO was conducted. In other ratios, namely debt to equity ratio (DER), debt to assets ratio (DAR), return on equity (ROE) and total assets turnover (TAT) there is a decrease in the value of the ratio even though it is not significant after the IPO.The conclusion taken in this study is the financial performance of manufacturing companies that IPO in 2015 on the ratio of current ratio (CR), quick ratio (QR), debt to equity ratio (DER), debt to assets ratio (DAR), return on assets (ROA), net profit margin (NPM), and working capital turnover (WCT) experienced an increase in the company's financial performance after the IPO, while the return on equity (ROE) and total assets turnover (TAT) ratio decreased the company's financial performance after the IPO.